Elevated IgG Responses in Infants Are Associated With Reduced Prevalence of Mycobacterium tuberculosis Infection - Logan, Erin; Luabeya, Angelique Kany Kany; Mulenga, Humphrey; Mrdjen, Dunja; Ontong, Cynthia; Cunningham, Adam F.; Tameris, Michele; McShane, Helen; Scriba, Thomas J.; Horsnell, William G. C.; Hatherill, Mark (Frontiers in Immunology, 2018)
Background: It is unclear whether antibodies can prevent Mycobacterium tuberculosis (Mtb) infection. In this study, we examined the relationship between total plasma IgG levels, IgG elicited by childhood vaccines and soil-transmitted helminths, and Mtb infection prevalence, defined by positive QuantiFERON (QFT) test. Methods: We studied 100 Mtb uninfected infants, aged 4-6 months. Ten infants (10%) converted to positive QFT test (QFT+) within 2 years of follow-up for Mtb infection. Antibody responses in plasma samples acquired at baseline and tuberculosis (TB) investigation were analysed by enzyme-linked immunosorbent assay (ELISA) and ImmunoCAP® assay. Results: QFT- infants displayed a significant increase in total IgG titres when re-tested, compared to IgG titres at baseline, which was not observed in QFT+ infants. BCG vaccine-specific IgG2 and live-attenuated measles vaccine-specific IgG were raised in QFT- infants, and infants who acquired an Mtb infection did not appear to launch a BCG-specific IgG2 response. IgG titres against the endemic helminth Ascaris lumbricoides increased from baseline to QFT re-testing in all infants. Conclusions: These data show raised IgG associates with a QFT-status. Importantly this effect was also associated with a trend showing raised IgG titres to BCG and measles vaccine. Our data suggests a possible protective association between raised antibody titres and acquisition of Mtb infection, potentially mediated by exposure to antigens both related and unrelated to Mtb.